Synthesis and photovoltaic properties of main chain polymeric metal complexes containing 8‐hydroxyquinoline metal complexes conjugating alkyl fluorene or alkoxy benzene by CN bridge for dye‐sensitized solar cells. Issue 10 (2nd July 2013) - Jin, Xueliang; Yu, Xiaoguang; Zhang, Wei; Zhou, Jun; Tang, Guipeng; Zhong, Chaofan
<x xml:space="preserve">Abstract</x> Four main chain polymeric metal complexes (P1–P4) based on 8‐hydroxyquinoline metal complexes have been synthesized by the Heck coupling and characterized by gel‐permeation chromatography, Fourier transform infrared spectroscopy, proton‐nuclear magnetic resonance, thermogravimetric analysis, ultraviolet–visible absorption, photoluminescence spectroscopy, elemental analysis, and cyclic voltammetry. The applications of these polymers as dye sensitizers in dye‐sensitized solar cells (DSSCs) are also studied. The study results show that the solar cells have good device performance with power conversion efficiency of P1–P4 up to 2.17, 2.04, 2.45, and 2.18%, respectively. The highest power conversion efficiency of DSSCs is up to 2.45%, for P3 consisting of alkoxy benzene unit and Cd–metal complex under the illumination of air mass 1.5 G, 100 mW cm−2. POLYM. COMPOS., 34:1629–1639, 2013. © 2013 Society of Plastics Engineers